Audit Energi dan Redesign Instalasi Listrik di TVRI Sulut - Merari Manoa; Meita Rumbayan; Hans Tumaliang (Universitas Sam Ratulangi, 2019)
Abstrack—Energy audit is a method used to calculate the amount of energy consumption in a building. Installation of electrical installations that are in accordance with the standards must use the general requirements of electrical installations, the Indonesian National Standard and the aesthetics of installation neatness. The energy audit and redesign of the electricity installation on TVRI North Sulawesi aims to determine energy use, energy utilization conditions, and to solve the electrical installation problems as far as possible on TVRI in the form of neat and irregular electricity installation networks, so that the load sharing is not balanced and the difficulty of carrying out maintenance under fault conditions. Keywords— Electric Energy: Energy Audit: Redesign of electrical installation: TVRI North Sulawesi. Abstrak—Audit energi adalah metode yang dipakai untuk menghitung besarnya konsumsi energi pada bangunan gedung. Instalasi listrik membantu menyalurkan energi listrik agar dapat digunakan oleh konsumen. Pemasangan instalasi listrik yang sesuai standar harus menggunakan persyaratan umum instalasi listrik (PUIL), Standart Nasional Indonesia (SNI) serta estetika kerapihan pemasangan. Audit energi dan redesign instalasi listrik di TVRI Sulawesi Utara bertujuan untuk mengetahui penggunaan energi, Kondisi pemanfaatan energi, dan untuk sebisa mungkin menyelesaikan masalah instalasi listrik yang terdapat di TVRI Sulawesi Utara berupa jaringan instlasi listrik yang tdak rapih dan tidak teratur, sehingga pembagian beban tidak seimbang dan sulitnya melakukan maintenance pada kondisi gangguan. Kata Kunci— Energi Listrik: Audit Energi: Redesign instalasi listrik: TVRI Sulut.